2016
DOI: 10.3390/molecules21101322
|View full text |Cite
|
Sign up to set email alerts
|

Natural and Synthetic Coumarins with Effects on Inflammation

Abstract: Abstract:In this review, we will present the different aspects of coumarins and derivatives, from natural origins or synthetically prepared, and their action on inflammation. Coumarins and also furo-and pyranocoumarins are found in many different plants. These compounds are very often investigated for antioxidant properties. Other biological properties are also possible and anti-inflammation activity is one of these. As coumarins are also available quite easily via synthesis, natural ones can be prepared this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
74
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 50 publications
0
74
0
2
Order By: Relevance
“…Thus, the use of antioxidant drugs as a scavenger of free radicals may reduce the extent of myocardial damage [34]. Recently, several coumarins based [14,35,36]. Hence, our study investigated the effects of precotreatment with (E)-N ′ -(1-(7hydroxy-2-oxo-2H-chromen-3-yl) ethylidene) benzohydrazide, a potent synthesized hydrazone coumarin, on the changes in oxidative parameters and cardiac biomarkers levels, myocardial proapoptotic and antiapoptotic factors, and the modification on histopathological parameters and heart function, during ISO-induced MI in rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the use of antioxidant drugs as a scavenger of free radicals may reduce the extent of myocardial damage [34]. Recently, several coumarins based [14,35,36]. Hence, our study investigated the effects of precotreatment with (E)-N ′ -(1-(7hydroxy-2-oxo-2H-chromen-3-yl) ethylidene) benzohydrazide, a potent synthesized hydrazone coumarin, on the changes in oxidative parameters and cardiac biomarkers levels, myocardial proapoptotic and antiapoptotic factors, and the modification on histopathological parameters and heart function, during ISO-induced MI in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Coumarins are found in several plant families and essential oils and are used as fragrant additives in food and cosmetics [12]. Many reports have suggested that the coumarins possess a huge array of biological roles, such as antithrombotic, neuroprotective, antidiabetic, anticoagulant, anti-inflammatory, antioxidant, and antiplasmodial activities [13][14][15][16][17][18][19]. Due to technical advancement, the coumarins and its derivatives are becoming a potential source for new drug discovery [20].…”
Section: Introductionmentioning
confidence: 99%
“…[9] Moreover, various coumarin-related derivatives serve as inhibitors of the lipoxygenase and cyclooxygenase pathways of arachidonate metabolism. [10,11] Given its favorable antiinflammatory activity, a coumarin framework has been used for chemical modification for identifying novel derivatives with improved pharmacological or pharmacokinetic profiles.…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, extracts used externally have been shown to reduce skin inflammation and edema (Kwon et al, 2011). Derivatives such as esculetin, fraxetin and daphnetin exhibit antioxidant activity, acting as inhibitors of the lipoxygenase and cyclooxygenase enzyme pathways (Kirsch et al, 2016). In vitro studies on coumarin compounds have served to demonstrate their antimicrobial and antifungal activity.…”
Section: Introductionmentioning
confidence: 99%